Comprehensive Evaluation of Waterflooding Performance with Induced Fractures in Tight Reservoir: A Field Case. (24th February 2021) - Feng, Naichao; Chang, Yuwen; Wang, Zuoqian; Liang, Tao; Guo, Xiaofei; Zhu, Yimeng; Hu, Limin; Wang, Yang
Abstract : Whether intentionally or unintentionally, waterflooding always takes place under fracturing condition in tight reservoir because of the extremely limited water absorption ability of the formation. Recently, we proposed a novel workflow, including real-time monitoring, formation testing analysis, and dynamic production analysis, to timely and effectively identify the initiation of waterflood-induced fractures (WIFs) and characterize the waterflooding behaviors for a well group. In this paper, we further provide a supplementary study to evaluate the waterflooding performance from the well group to the field basis. The utilization factor (UF) is first estimated on the basis of injection/production data by material balance theory, which provides an overall picture of water injection efficiency every year. Then, the areal (straightforwardly showed by water cut and formation pressure distributions) and vertical sweep (includes the water absorption in injectors and water breakthrough in producers) behaviors are studied to investigate the waterflooding characteristics and residual oil distributions. Lastly, three key influence factors are detailedly discussed: sand body connectivity, WIFs, and injection and production correspondence. Combining the previous work for the single well group, and the study in this paper to field basis, one can have a better and much more comprehensive understanding of the waterflooding performance and then thus take the corresponding adjustment measurements to improve waterflooding effectiveness.